(untitled) (English Language and Literature (JELL), 2026)
This study aims to analyze and compare the use of figurative language in Donald Trump’s 2016 and 2024 presidential debates. Figurative language plays an essential role in shaping meaning, creating emphasis, and enhancing persuasion in political communication. Using Perrine’s (1977) theory of figurative language, this research identifies and categorizes eleven types of figurative expressions: hyperbole, irony, understatement, apostrophe, synecdoche, metonymy, paradox, symbolism, simile, metaphor, and personification. The study adopts a descriptive analysis method, using the official debate transcripts from both election periods as the primary data sources. The findings reveal that Trump employed nine types of figurative language in the 2016 debates—dominated by hyperbole, personification, and metaphor—while in the 2024 debates, he used only seven types, with a significant increase in hyperbolic expressions. The absence of certain figurative types, such as synecdoche and paradox, suggests that Trump favors direct, emphatic, and emotionally charged language over abstract or subtle forms. Comparatively, his 2024 debates show a higher reliance on exaggeration and symbolic simplification, reflecting a shift toward a more sensational and emotionally driven rhetorical style. Overall, this study concludes that Trump’s use of figurative language demonstrates a consistent preference for vivid, persuasive, and accessible speech designed to appeal to public emotion and reinforce his populist image. The results contribute to the field of linguistics by providing insight into how figurative language functions as a rhetorical device in political debates.